Annular Pancreas: A Rare Cause of Acute Pancreatitis - Jarry, Julien; Wagner, Tristan; Rault, Alexandre; Sa Cunha, Antonio; Collet, Denis (JOP. Journal of the Pancreas, 2011)
Context Annular pancreas is an uncommon and rarely reported congenital anomaly which consists of a ring of pancreatic tissue encircling the duodenum. Despite the congenital nature of the disease, clinical manifestations may ensue at any age. Case report We herein report the case of a 72-year-old female with acute pancreatitis associated with duodenal obstruction. On radiologic examination, an annular pancreas was diagnosed. In view of her previous medical history and morphologic findings, we concluded that the acute pancreatitis was directly related to the congenital anomaly. Her clinical course was favorable after medical treatment. Conclusion Clinicians should note the possibility of annular pancreas in patients with acute pancreatitis. Image: Double contrast barium radiography showing stenosis of the second duodenum.